Butterfly story - Hariton, Anca. (New York : Dutton Children's Books, 1995)
Simple text and colorful illustrations introduce children to the stages in the life of a butterfly. Shows how an egg becomes caterpillar, and pupa, and at long last a butterfly.
Wilson's Children.
School Library Journal.
Child Study Children's Book Committee.
2.9
K-3
Keywords: Butterflies -- Life cycles -- Juvenile literature; Butterflies -- Juvenile literature; Butterflies; Caterpillars; Butterflies; Caterpillars; Butterflies -- Life cycles; Butterflies; Caterpillars